Сross-platform application for NFT tokens - Hladka, Olena Mykolayivna; Karpovich, Ivan; Opanasiuk, Mykhailo (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2023)
A software application has been developed, which is a platform for creating, storing, viewing and selling NFT tokens. The object of research is the process of managing NFT tokens, the subject of research is the development and implementation of the NFT token marketplace. The developed application is a micro service that includes an API for working with NFT tokens and a client part that provides a convenient way to use the marketplace for users. The backend part was developed in the C# programming language, and the frontend part uses React and Redux. OOP methods, the Git version control system, namely Github, work with multithread, asynchrony and implemented SOLID principles were used during development. The application allows users to access NFT tokens, perform various operations with them and manage tokens. The libraries used in the application ensure stability and security in the process of working with tokens. This application allows for efficient and secure exchange of NFT tokens between different systems and users. The developed software product is built according to the principle of Clean Architecture, which will provide easy further expansion of the scope of the project.